Budidaya Sorgum (Sorghum bicolor L. Moench) Sebagai Alternatif Penyediaan Pakan Ternak Berkelanjutan - Riesi Sriagtula; Yetmaneli Yetmaneli; Ida Indrayani; Ridho Kurniawan Rusli (Warta Pengabdian Andalas, 2022)
The cow farmer in Padang was changed from semi-intensive to intensive because of city development. The intensive system requires farmers to be forage feeding cut and carried from field margins. The limited knowledge of smallholder farmers about the high quality of forage causes native grass to become the primary source of forage; meanwhile, the low nutrient content of native grass causes the low production and reproduction in cows. To overcome the adequacy of feed forage, both in quality and quantity, thus cultivation of forage was conducted on unproductive land such as peatlands. Generally, peatland with a shallow category and low pH is widespread on the coast of Padang city. Sorghum is tolerant to acid soil and can be the solution to overcome forage feeding in the dry season. The community service activities were carried out from October 2021 until January 2022 and aimed to increase farmers' knowledge in feed diversification and skills in cultivating sorghum as a superior feed crop. The activities were conducted using counselling and discussion methods and the practice of sorghum cultivation on peatlands. Results showed that cow farmers know the importance of providing quality sustainable forage to increase livestock productivity, especially brood cows. The conclusion is that sorghum can be a substitute for native grass and as a concentrate; hence it can be an alternative solution to the problem of supplying feeding in Padang city.